ChemInform Abstract: Efficient Synthesis of 9‐Aryldihydrophenanthrenes by a Cascade Reaction Involving Arynes and Styrenes. Issue 26 (1st July 2014) - Bhojgude, Sachin Suresh; Bhunia, Anup; Gonnade, Rajesh G.; Biju, Akkattu T.
Abstract Arynes generated from triflates (II) and (IV) undergo a cascade reaction initiated by a Diels—Alder reaction with styrenes to form the title phenanthrene derivatives.